Pengaruh Kepemimpinan Manajerial Dan Ketersediaan Sarana Digital Terhadap Kompetensi Profesional Guru Anggota KKG Di Gugus XV Kota Lubuklinggau - Saputra, Musa; Nur Sasongko, Rambat; Connie (UNIVERSITAS BENGKULU, 2024)
The purpose of the study was to analyze the effect of managerial leadership and the availability of digital facilities on teacher professional competence. This study used an associative quantitative approach. The study population was 78 teachers who were members of KKG in Gugus XV Lubuklinggau City. The sampling technique was carried out using saturated sampling technique with a research sample of 78 people. Data collection techniques using a questionnaire. Data analysis techniques using Determination test analysis (R2). Research results 1) There is an influence of managerial leadership on the professional competence of teachers by 12.8%. 2) There is an influence of the availability of digital facilities on the professional competence of teachers by 26.8%. 3) There is an influence of managerial leadership and the availability of digital facilities together on the professional competence of teachers by 32.2%. While the other 67.8% is influenced by other factors such as educational background, motivation, work experience and knowledge.